Penerapan Metode Pembelajaran STAD (Student Teams Achivement Division) Berbantuan Aplikasi Filmora untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI di SMAN 1 Cigugur - Putri, Keysha Adilla; Lutfi, Ahmad Fajri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to increase student learning motivation through the application of the STAD (Student Teams Achivement Division) method using the filmora application as a support. This study uses a quantitative method with a Quasi Experimental approach and a Pretest-Posttest Control Design design implemented in SMA Negeri 1 Cigugur with 308 students. The sample of this research was class XI-1 as the experimental class and class XI-3 as the control class. Data were collected using pretest and posttest questionnaires on learning motivation, observation and documentation. Data were analyzed descriptively quantitatively. The results of the study revealed a significant difference in learning motivation between the conventional method and the STAD method assisted by the filmora application, stated through hypothesis testing with a t-test. The average posttest value of the control class was 74,41, while the experimental class was 80,23 with a difference of 5,82. It is known that the calculated t value of 6,380 is greater than the t table of 1,996 (6,380 > 1,996), so H1 is accepted and H0 is rejected.